Shear Bond Strength at the Resin/Bracket Interface of Sandblasted Brackets with Different Aluminum Oxide Particle Size - Abad Bocangel Salcedo-Alcaychahua; Aron Aliaga-Del Castillo; Luis Ernesto Arriola-Guillén (Journal of Orofacial Sciences, 2020)
Introduction: The aim of this study was to compare the shear bond strength at the resin/bracket interface of metal brackets sandblasted with aluminum oxide particles of 25 µm, 50 µm and 110 µm. Materials and Methods: Sixty metal brackets were recycled and randomly assigned into four groups according to the aluminum oxide (Al2O3) particle size (µm) used during sandblasting. Brackets of the first three groups (Group 1, n = 15; Group 2, n = 15 and Group 3, n = 15) were sandblasted with 25µm, 50µm, and 110µm Al2O3 particle size, respectively. The control group (Group 4, n = 15) included brackets without sandblasting. Shear bond strength was evaluated before and after sandblasting. Brackets with some variation in shape or structure were excluded. Intragroup and intergroup comparisons were performed with paired t-test and one-way analysis of variance (ANOVA) followed by Scheffé test, respectively. Results: The recycled sandblasted brackets showed greater shear bond strength approximately 4 to 6 Mpa more than those that did not receive sandblasting. There were no statistically significant differences between the sandblasted groups (P > 0.05). However, Group 3 (110µm) showed a numerically greater mean value of shear bond strength (9.34 ± 4.18 Mpa). Conclusion: Similar share bond strength at the resin/bracket interface can be expected after bracket sandblasting with 25µm, 50µm, and 110µm Al2O3 particle size. Independently of the particle size used, the sandblasted brackets showed greater shear bond strength than brackets without sandblasting.